(untitled) (Fiep Bulletin - online, 2013)
The study of the central corporal temperature is study object of the physiology at a long time and it has been showing if decisive in the point of emergence of the fatigue intra-effort. Several studies are led with different methodologies, however the use of a method little perfected and I need it interferes in the obtained results and it limits the conclusions. The present study analyzed some of the different methods used in research, relating the readiness and efficiency of each one. It is intended with the study to determine which method is the perfected and starting from this method to supply a tool for development of a necessary method, perfected and of cost relatively low and this way to enlarge the studies in this research area.